Dopamine Genetics: Substance Use Disorders vs. Parkinson’s Disease - Z. Carl Lin; F. S. Hall; R. L. Bell (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
It is established that Substance use disorders (SUDs) and Parkinson’s Disease (PD) among many other neuropsychiatric disorders are dopamine (DA)-related brain disorders with strong heritability. However, it is unclear whether DA-associated genetic risks share commonality across these disorders. This study utilizes the Genotype and Phenotype Database (dbGaP), by downloading related genome-wide association studies (GWAS) for individual genotype/phenotypes. According to our results DA pathways are significantly implicated in the genetic etiology of both SUDs and PD but much more in the former. Epistatic effects may represent a major portion of missing heritability observed in current main effect-oriented GWAS analyses.